2005
DOI: 10.1002/jmri.20311
|View full text |Cite
|
Sign up to set email alerts
|

Multisite trial of MR flow measurement: Phantom and protocol design

Abstract: Purpose: To describe a portable, easily assembled phantom with well-defined bore geometry together with a series of tests that will form the basis of a standardized quality assurance protocol in a multicenter trial of flow measurement by the MR phase mapping technique. Materials and Methods:The phantom consists of silicone polymer layers containing parallel straight and stenosed flow channels in one layer and a U-bend in a second layer, separated by hermetically sealed agarose slabs. The phantom is constructed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…Dynamic threedimensional balanced turbo field echo (3D B-TFE) and 2D B-TFE images were acquired in 15 phases of the cardiac cycle (VCG triggered). The proximal boundary of the AAA model was determined from the 2D quantitative flow (Qflow, Summers et al, 2005) imaging plane, which was placed perpendicular to the vessel wall (directly below the renal arteries). A static recording of the AAA was made with a black blood (BB) protocol.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Dynamic threedimensional balanced turbo field echo (3D B-TFE) and 2D B-TFE images were acquired in 15 phases of the cardiac cycle (VCG triggered). The proximal boundary of the AAA model was determined from the 2D quantitative flow (Qflow, Summers et al, 2005) imaging plane, which was placed perpendicular to the vessel wall (directly below the renal arteries). A static recording of the AAA was made with a black blood (BB) protocol.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…The phantom can range from a simple tube to a dedicated anthropomorphic model [13]. Most pumps described in the literature have been either based on a motor-controlled gear pump design [5,7,10,11] or have used a commercial flow system (Shelley Medical Imaging Technologies, Ontario, Canada) [2,14]. Additional components (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies [ 9 13 ] have demonstrated excellent flow parameter agreement and improved volumetric velocity analysis when using 4D flow CMR compared to 2D PC CMR. In addition, several studies [ 14 16 ] have been performed to assess the reliability of flow measurements. However, to the best of our knowledge, no study has focused on the evaluation of peak velocity measured by 4D flow CMR in patients with TGA.…”
Section: Introductionmentioning
confidence: 99%